Influence of exercise intensity on time spent at high percentage of maximal oxygen uptake during an intermittent session in young endurance-trained athletes - Thevenet, D.; Tardieu, M.; Zouhal, H.; Jacob, C.; Abderrahman, B. A.; Prioux, J. (European Journal of Applied Physiology, 2007)
The purpose of this study was to compare, during a 30s intermittent exercise (IE), the effects of exercise intensity on time spent above 90% VO2max (t90 VO2max)VO2max(t90VO2max) and time spent above 95% VO2max (t95 VO2max)VO2max(t95VO2max) in young endurance trained athletes. We hypothesized that during a 30sIE, an increase in exercise intensity would allow an increase in t90 VO2max and t95 VO2maxt90VO2maxandt95VO2max due to a decrease in time to achieve 90% or 95% of VO2max.VO2max Nine endurance-trained male adolescents took part in three field tests. After determination of their VO2maxVO2max and maximal aerobic velocity (MAV), they performed, until exhaustion, two intermittent exercise sessions alternating 30s at 100% of MAV (IE100) or 110% of MAV (IE110) and 30s at 50% of MAV. Mean time to exhaustion (t lim) values obtained during IE100 were significantly longer than during IE110 (p < 0.01). Moreover, no significant difference was found in VO2max or t95 [V\dot]O2maxt90VO2maxort95VO2max expressed in absolute or relative (%t lim) values between IE100 and IE110. In conclusion, an increased of 10% of exercise intensity during a 30s intermittent exercise model (with active recovery), does not seem to be the most efficient exercise to solicit oxygen uptake to its highest level in young endurance-trained athletes.